Notas introductorias sobre Gramsci (2008)
This work is an introduction to the study of Antonio Gramsci`s political thought. Gramsci’s life complexity and the historical reality, in which he thinks and moves, made Gramsci’s Marxism a particular political line, different from the MarxistLeninist point of reference. Gramsci’s Marxism is at the present time the most influential expression of Marxism in the Western world. His thoughts about hegemony, political and civil society are the result of a conception which intertwines political work with cultural work.